2022
DOI: 10.1002/smll.202200550
|View full text |Cite
|
Sign up to set email alerts
|

Eutectic Electrolytes Chemistry for Rechargeable Zn Batteries

Abstract: Rechargeable zinc batteries (RZBs) have proved to be promising candidates as an alternative to lithium‐ion batteries due to their low cost, inherent safety, and environmentally benign features. While designing cost‐effective electrolyte systems with excellent compatibility with electrode materials, high energy/power density as well as long life‐span challenge their further application as grid‐scale energy storage devices. Eutectic electrolytes as a novel class of electrolytes have been extensively reported and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 136 publications
0
36
0
Order By: Relevance
“…[15,16] Unlike conventional electrolytes with solvated cations and anions through simple dissolving, the eutectic electrolytes contain complex anions and cations, which are formed through the strong interactions between the components. [17][18][19] For example, 2.0 M ZnCl 2 aqueous electrolyte contains solvated Zn ] + cations. [20] Compared with the traditional electrolytes, the eutectic electrolytes possess many characteristics, such as structural flexibility, good thermal/chemical stability, low vapor pressure, and wide potential windows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15,16] Unlike conventional electrolytes with solvated cations and anions through simple dissolving, the eutectic electrolytes contain complex anions and cations, which are formed through the strong interactions between the components. [17][18][19] For example, 2.0 M ZnCl 2 aqueous electrolyte contains solvated Zn ] + cations. [20] Compared with the traditional electrolytes, the eutectic electrolytes possess many characteristics, such as structural flexibility, good thermal/chemical stability, low vapor pressure, and wide potential windows.…”
Section: Introductionmentioning
confidence: 99%
“…When DESs is applied as the electrolyte for batteries, it is usually called eutectic electrolyte [15, 16] . Unlike conventional electrolytes with solvated cations and anions through simple dissolving, the eutectic electrolytes contain complex anions and cations, which are formed through the strong interactions between the components [17–19] . For example, 2.0 M ZnCl 2 aqueous electrolyte contains solvated Zn 2+ cations and Cl − anions, while AlCl 3 /acetamide (AcA) eutectic electrolyte has AlCl 4 − and Al 2 Cl 7 − anions and [AlCl 2 (AcA) 2 ] + cations [20] .…”
Section: Introductionmentioning
confidence: 99%
“…[53][54][55][56] Though a few varieties of anodes exist in the form of galvanized and zinc-free anodes, the most widely used anode material is still pure zinc foil so far. [57][58][59] The reliability and reversibility of Zn akes are vital to achieve outstanding performance of ZMBs. [60][61][62][63][64][65][66] However, some issues and challenges including the dendrite growth and shape change, gassing, corrosion, and passivation caused by the harsh HER side reaction with aqueous electrolytes still remain, limiting their actual applications.…”
Section: Challenges Of Zmasmentioning
confidence: 99%
“…However, this eutectic electrolyte-designed approach still faces challenges associated with eutectic component selection and composition collocation. 12 Considering its infancy stage, eutectic-solvent systems require a pivotal study of novel "eutectic regime" dedicated to the molecular structure transition from ordinary "diluted solutions" to unique "solvent-ineutectic" domination. 13 To circumvent the challenges above, most recent studies have demonstrated "water-in-DES" (WiDES) 14 and hydrated eutectic electrolytes 15 through the precise regulation of H 2 O content to suppress water activity and facilitate ion transport.…”
Section: Introductionmentioning
confidence: 99%
“…However, this eutectic electrolyte-designed approach still faces challenges associated with eutectic component selection and composition collocation. 12 Considering its infancy stage, eutectic-solvent systems require a pivotal study of novel “eutectic regime” dedicated to the molecular structure transition from ordinary “diluted solutions” to unique “solvent-in-eutectic” domination. 13…”
Section: Introductionmentioning
confidence: 99%